Pharmacophore modeling, 3D‐QSAR, synthesis, and anti‐lung cancer evaluation of novel thieno[2, 3‐d][1, 2, 3]triazines targeting EGFR. Issue 2 (2nd January 2020) - Elrayess, Ranza; Abdel Aziz, Yasmine M.; Elgawish, Mohamed S.; Elewa, Marwa; Elshihawy, Hosam A.; Said, Mohamed M.
Abstract: Two series of thieno[2, 3‐ d ][1, 2, 3]triazine derivatives were designed, synthesized, and biologically evaluated as potential epidermal growth factor receptor (EGFR) inhibitors targeting the non‐small‐cell lung cancer cell line H1299. Most of the synthesized compounds displayed IC50 values ranging from 25 to 58 nM against H1299, which are superior to that of gefitinib (40 µM). 3‐(5, 6, 7, 8‐Tetrahydro‐7 H ‐cyclohexa[4:5]thieno[2, 3‐ d ]‐1, 2, 3‐triazin‐4‐ylamino)benzene‐1, 3‐diamine (6b ) achieved the highest cytotoxic activity against H1299 with an IC50 value of 25 nM; it had the ability to decrease the EGFR concentration in H1299 cells from 7.22 to 2.67 pg/ml. In vitro, the IC50 value of compound 6b was 0.33 nM against EGFR, which is superior to that of gefitinib at 1.9 nM and erlotinib at 4 nM. The three‐dimensional quantitative structure–activity relationships and molecular modeling studies revealed comparable binding modes of compound 6b, gefitinib, and erlotinib in the EGFR active site. The in silico ADME (absorption, distribution, metabolism, and excretion) prediction parameters of this compound revealed promising pharmacokinetic and physicochemical properties. Moreover, DFT (density functional theory) calculations showed the high reactivity of compound 6b toward the EGFR compared with other compounds. The designed compound 6b might serve as an encouraging lead compound for the discovery of promising anti‐lung cancer agents targeting EGFR. Abstract : Two series of thieno[2, 3‐ d ][1, 2, 3]triazine derivatives were designed, synthesized, and evaluated as potential epidermal growth factor receptor (EGFR) inhibitors targeting the non‐small‐cell lung cancer cell line H1299. The three‐dimensional quantitative structure–activity relationships and molecular modeling studies revealed comparable binding modes of the most active compound 6b, gefitinib, and erlotinib in the EGFR‐active site. 6b might serve as an encouraging lead compound for the discovery of promising anti‐lung cancer agents targeting EGFR